KEPERCAYAAN (TRUST) PADA ANGGOTA KOMUNITAS PEREMPUAN NELAYAN DI DESA LAMBANGI KECAMATAN KOLONO TIMUR KABUPATEN KONAWE SELATAN - Nasyratullah, Fadillah; Abdullah, Sukmawati; Salahuddin, Salahuddin (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2024)
One element of social capital that plays an important role in community resilience is trust. When community members trust each other, they are better able to weather crises and adapt to unexpected changes. Therefore, trust within a community must be maintained in order to overcome various challenges that may arise, including economic vulnerability. This study aims to assess the level of trust in members of the fisherwomen community in Lambangi Village, East Kolono Sub-district, South Konawe Regency. The study population consisted of all female fish processors of anchovies, with a total of 32 individuals. The sample determination employed the saturated sampling technique or census, whereby the entire population was taken as a sample, namely 32 people. Data were collected through interviews, surveys, and documentation, with the assistance of questionnaires. This study employed a quantitative approach in its completion. Data were processed using descriptive quantitative analysis through the use of the class interval formula. The findings indicated that the level of trust among the fisherwomen community members in Lambangi Village was high. This suggests that the fisherwomen have effectively implemented every aspect of trust, namely aspects of openness, sharing, acceptance, support, and cooperation within the community of fisherwomen in Lambangi Village.